2016
DOI: 10.1097/mpg.0000000000000929
|View full text |Cite|
|
Sign up to set email alerts
|

Durability of Response in Children Treated With Pegylated Interferon alfa‐2a ± Ribavirin for Chronic Hepatitis C

Abstract: Objectives:No long-term data have been published on the durability of response following pegylated interferon (PegIFN) treatment in children with chronic hepatitis C (CHC). This prospective, multi-center, long-term follow-up (LTFU) study aimed to assess long-term durability of sustained virological response (SVR), long-term safety and tolerability, and the association between IL28B genotype and treatment response, in children previously treated with PegIFN alfa-2a ± ribavirin (RBV) in the PEDS-C trial.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…Despite well‐established guidelines for treating HCV in adults, there is no universal consensus on when or if to treat chronic HCV infection in children. Treatment of pediatric patients has been controversial as the current standard of care, pegylated interferon and weight‐based ribavirin, is associated with significant side effects, including growth impairment, and poor tolerability …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite well‐established guidelines for treating HCV in adults, there is no universal consensus on when or if to treat chronic HCV infection in children. Treatment of pediatric patients has been controversial as the current standard of care, pegylated interferon and weight‐based ribavirin, is associated with significant side effects, including growth impairment, and poor tolerability …”
Section: Discussionmentioning
confidence: 99%
“…Treatment of pediatric patients has been controversial as the current standard of care, pegylated interferon and weight-based ribavirin, is associated with significant side effects, including growth impairment, and poor tolerability. (10)(11)(12) In adults, all-oral, direct-acting HCV regimens offer the benefits of greater tolerability, improved response rates, fewer adverse events, easier administration, and shorter duration relative to pegylated interferon and ribavirin. (23) Multiple direct-acting HCV regimens are available for adults with HCV genotype 1 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pooled data from five studies, 93% of 73 children with HCV genotype 2 or 3 achieved sustained virologic response with 24 weeks of peginterferon and ribavirin . Response is durable, as indicated by a follow‐up study of 21 responders 4‐7 years after treatment . However, because of the potential for tolerability issues and growth impairment with peginterferon and ribavirin, there is no universal consensus on when or if to treat chronic HCV infection in children with these agents.…”
mentioning
confidence: 99%
“…Several studies have suggested that certain factors may predict a more favorable response to PEG‐IFN/RBV therapy, including host characteristics, such as the interleukin 28B polymorphisms, having genotype 2 or 3, and mode of transmission (iatrogenic versus vertical transmission) 114, 119, 120, 121, 122. Ultimately, the current standard of care in the treatment of HCV‐infected children with IFN and RBV regimens with their well‐documented toxicities, inconvenient modes of administration (subcutaneous IFN injections), longer durations of treatment, and poor overall efficacy often leaves pediatric hepatologists searching for alternatives.…”
Section: Managementmentioning
confidence: 99%